2005
DOI: 10.1515/epoly.2005.5.1.621
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermodynamic modelling of Pluronic L64 solutions

Abstract: Abstract:The aim of the present work is to model structure and thermodynamic properties of Pluronic L64 solutions (triblock copolymer with hydrophilic ends and a hydrophobic middle). We first determined the micelle size by dynamic light scattering at various temperatures. This helps to understand the particle formation mechanism in solution and the interparticle interactions by following the virial coefficient as well as its temperature dependence. Two semi-empirical intermolecular potentials were tested to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6] These copolymers have a symmetrical structure (PEO) n (PPO) m (PEO) n where n and m denote the number of ethylene oxide and propylene oxide monomers per block and they are commercially available under trade names such as Pluronic (BASF), Synperionic (ICI), or Poloxamer, as a more general name. [7] They consist of hydrophobic (PPO) and hydrophilic (PEO) blocks, which aggregate in aqueous solutions forming structures well known as micelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] These copolymers have a symmetrical structure (PEO) n (PPO) m (PEO) n where n and m denote the number of ethylene oxide and propylene oxide monomers per block and they are commercially available under trade names such as Pluronic (BASF), Synperionic (ICI), or Poloxamer, as a more general name. [7] They consist of hydrophobic (PPO) and hydrophilic (PEO) blocks, which aggregate in aqueous solutions forming structures well known as micelles.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Hence, the literature has had considerable confusion concerning the association properties of Pluronic in aqueous solution. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, McDonald and Wong, [16] using static light scattering, indicated that there was no association detectable in aqueous solution in the range of temperature 25 • C-40 • C. On the other hand, on the basis of photon correlation spectroscopy and viscosity measurements, A1-Saden et al [4] reported that aqueous Pluronic solutions showed detectable aggregates at 25 • C and higher temperatures. Some PEO-PPO-PEO copolymers are also reorganized to form gels in water.…”
Section: Introductionmentioning
confidence: 99%
“…At T = 313 K, it is possible that the critical micelle temperature (CTC) occurs . At T = 319 and 331 K, as reported for L64 + water systems, second virial coefficient calculations show a change in slope, indicating that water becomes a poorer solvent at this temperature . On the other hand, micelles can modify from globular to rod and the system can even form a gel at higher temperatures.…”
Section: Resultsmentioning
confidence: 76%
“…Those changes attributed to cloud point phase transition can be verified at approximately T = 293 and 313 K. Fade point transition is attributed to occur near the maximum value of α T observed (T = 298 K); • The L35 + water system is denser than PPG 400 and PE62 due to the smaller content of PPG units (as shown in Table 2). Here, three changes in slope can be observed in the α T plot, at T = 313, 319, and 331 K. Since no cloud point transition was observed within this temperature range (Figure 7a), these changes are attributed to micelle 109 or gel 94 formation. At T = 313 K, it is possible that the critical micelle temperature (CTC) occurs.…”
Section: Resultsmentioning
confidence: 82%
“…The triblocks copolymers based on poly(ethylene oxide)poly(propylene oxide)-poly(ethylene oxide), usually named Pluronics (manufactured by BASF) or Poloxamers (manufactured by ICI), are able to form direct micelles with PEO coronas and PPO cores or reverse micelles with PEO cores and PPO coronas under some conditions. The investigation of their association properties has had considerable ambiguity due to the fact that some of them are able to form direct micelles, reveres micelles, and various arrangements under several conditions, whereas some of them showed that the dimension of the structures formed was equal to the length of the hydrophobic stretched blocks [1][2][3][4][5][6][7][8][9]. In this regard, the critical micelle concentration, the critical micelle temperature, the aggregation number, and the polydispersity are usually given with a certain uncertainty [3].…”
Section: Introductionmentioning
confidence: 99%